Non-Publishers in European Universities - Kwiek, Marek (International Higher Education, 2015)
Most academics do not publish much, if anything. Yet, there is great emphasis on publishing in order to be promoted and respects in academe. This article provides analysis of the publication patterns of European academics, and shows that productivity is in fact quite low.